Choriocarcinoma: a rare case of stomach metastasis - Agarwal, Raju; Dharmesh, Col; Dey, Madhusudan; Pawar, Charu D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Choriocarcinoma is a rare form of cancer which commonly occurs in women of reproductive age, rarely in post-menopausal women and in women under 20 years of age. We report a rare case of uterine choriocarcinoma with stomach metastasis in a 29 year-old woman who presented with upper gastrointestinal symptoms. The presented case report emphasizes the need for innovative treatment approach and appropriate diagnostic technology to enable early diagnosis and correct treatment. Furthermore the case highlights the need for healthcare workers to consider rare causes of gastrointestinal signs and symptoms.